Mobile health: a synopsis and comment on “Increasing physical activity with mobile devices: a meta-analysis” - Johnston, Winter (Springer US, 2014)
We offer a synopsis and commentary on J. Fanning and colleagues’ article “Increasing Physical Activity with Mobile Devices: A Meta-Analysis” published in the Journal of Medical Internet Research. Although regular physical activity has a range of benefits, very few adults in the USA meet recommended guidelines for daily physical activity. The meta-analysis of Fanning et al. (2012) aimed to synthesize the results of research using mobile devices to increase physical activity. Their review identified 11 studies that used mobile technologies, including short message service (SMS), apps, or personal digital assistant (PDA) to improve physical activity behaviors among participants. Fanning et al. conclude that while literature in this area is limited to date, there is initial support for the efficacy of mobile-based interventions for improving physical activity. Included studies varied greatly, and the majority used only SMS to influence physical behaviors, meaning generalization of results to other forms of mobile technologies may be premature. This review does, however, provide a foundation for understanding how mobile-based interventions may be used efficaciously for the development of future interventions to improve health behaviors.